The Effect of Psych Education on Post Partum Depression in the Syech Yusuf Gowa Hospital, Indonesia - Nuraeni Mustari; Hariani; Ningsih Jaya; Baharuddin K; M. Askar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: The purpose of this study was to analyze the effect of Psych education on the incidence of postpartum depression at Syech Yusuf Gowa Hospital.Method: This study was a quasi experimental with pre-post test design. The population in this study werepostpartum mothers hospitalized in the Syech Yusuf Gowa Hospital Indonesia during research conducted.The amounted 30 subjects participated were taken by simple random sampling. Data were analyzed bypaired sample t-test using SPSS for windows.Result: The results showed that there was significantly influence of the provision of Psych education on postpartum depression in Syech Yusuf Gowa Regional Hospital with p=0.002 based on statistical test results.Conclusion: Psych education should be followed up every day to see the mother’s progress in overcomingdepression.